An Analysis of the Relationship between Cultural- Cinematic Policies of Iran and the Movies Introduced as the Representative of Iranian Cinema to the Academy of Oskar - Azam Ravadrad; Amirhossein Tamannaei (Taḥqīqāt-i Farhangī-i Īrān)
In this article the relationship between cultural policies and cinema in Iran is studied through a comparison between cultural-cinematic policies of two different Iranian states during years 1377 and 1389 and their effects on selecting the representative of Iranian cinema to the academy of Oskar. The theoretical framework of the study is based on the field of sociology of cinema, concentrating on Tony Bennett's theory relating to the effect of politics and state on form and content of cultural products. The methodology of the article is documentary and the technic used is qualitative content analysis. The analysis of cultural policies of cinema, as an issue in the field of sociology of cinema, shows that although form and content of movies are both influenced by social conditions, to which cultural policy is a part, form has been a more important criteria for the selection of movies to present in the academy of Oskar. In other words, there is a general policy in Iran that supports the idea of entering the competition of Oskar each year in order to show that Iranian cinema is so mature that is able to compete with the cinema of other countries. This policy leads to use the form and the aesthetic quality of movies as dominant criteria for the selection. Therefore, although based on each period's policies and state it is expected that selected movies produce some special contents, the importance of form has led to a selection of movies that are not directly appropriate with their co-existing domestic policies. Considering this interesting finding, it can be theoretically concluded that the effect of cultural policies on cinema is more on the content while the form of cinema is to a great extent free from the bounds of cultural policies.